REVITALISASI PEMBELAJARAN IPS MELALUI INTEGRASI KEARIFAN LOKAL MADURA DI SDN PARSANGA II - Muhammad Romli; I Wayan Kertih; I Wayan Lasmawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to revitalize Social Studies (IPS) learning in elementary schools through the integration of Madurese local wisdom as a contextual approach. The research was conducted at SDN Parsanga II, Sumenep Regency, involving two fourth-grade classes and two fifth-grade classes with a total of 80 students. A descriptive quantitative method was employed. The learning activities were designed around local cultural themes such as karapan sapi (bull racing), Madurese batik, saronen music, and fishing traditions. The results revealed a significant increase in student engagement and conceptual understanding of social studies after implementing the culture-based learning model. The students’ average scores improved with a mastery level ranging from 85% to 95%. These findings affirm the value of contextual learning rooted in local culture for enhancing the quality and relevance of social studies education. The study also presents practical implications for instructional material development, adaptive curriculum design, and culturally grounded educational policies.